1998
DOI: 10.1097/00005072-199812000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Sparc

Abstract: In an attempt to identify genetic alterations occurring early in astrocytoma progression, we performed subtractive hybridization between astrocytoma and glioblastoma cDNA libraries. We identified secreted protein acidic and rich in cysteine (SPARC), a protein implicated in cell-matrix interactions, as a gene overexpressed early in progression. Northern blot and immunohistochemical analyses indicated that transcript and protein were both elevated in all tumor specimens (grades II-IV) examined when compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(31 citation statements)
references
References 0 publications
3
27
0
Order By: Relevance
“…Its role in tumorigenesis has been examined in a variety of cancers (9,(35)(36)(37)(38) including hematological malignancies (12), with diverging actions that may be attributed to tissue-related differences. Previously, we demonstrated that SPARC gene and protein expression changes the sensitivity of therapy-refractory MIP101 CRC cells to chemotherapy in vitro and in vivo by enhancing apoptosis and tumor regression (9).…”
Section: Discussionmentioning
confidence: 99%
“…Its role in tumorigenesis has been examined in a variety of cancers (9,(35)(36)(37)(38) including hematological malignancies (12), with diverging actions that may be attributed to tissue-related differences. Previously, we demonstrated that SPARC gene and protein expression changes the sensitivity of therapy-refractory MIP101 CRC cells to chemotherapy in vitro and in vivo by enhancing apoptosis and tumor regression (9).…”
Section: Discussionmentioning
confidence: 99%
“…SPARC induces an intermediate stage of cellular adhesion with ablation of focal adhesions, regulates matrix deposition, and induces growth inhibition in endothelial cells (5,6,10). In addition to its normal physiological role, SPARC has been linked to cancer progression as many cancer types express increased SPARC levels upon invasion or metastasis (5,6,11,12). Malignant gliomas rarely metastasize but are highly invasive leading to a failure of curative surgery (13).…”
mentioning
confidence: 99%
“…Malignant gliomas rarely metastasize but are highly invasive leading to a failure of curative surgery (13). Gliomas express SPARC at sites of invasion and neoangiogenic blood vessels at the braintumor interface (11,14). We and others have shown that malignant glioma cell lines engineered to overexpress SPARC adopt an invasive phenotype both in vitro and in vivo associated with an increased expression of specific matrix metalloproteinases (15)(16)(17).…”
mentioning
confidence: 99%
“…28 We, therefore, compared the effects of 13cRA on CFU-GM growth from Mx1-Cre, Nf1 flox/flox and control bone marrows. As shown in Figure 3, Mx1-Cre, Nf1 flox/flox marrows contained elevated numbers of CFU-GM, which were larger than wild-type colonies.…”
Section: Resultsmentioning
confidence: 99%
“…The final step in Ras processing involves methylation of the prenylcysteine by isoprenylcysteine carboxyl methyltransferase (Icmt). Genetic experiments performed by Dr. Shannon's lab showed no detectable effects of ablating Rce1 on normal hematopoiesis (28).…”
Section: Technical Objective (Aim) 2: To Perform In Vitro and In Vivomentioning
confidence: 99%